The dopaminergic alterations induced by 4‐F‐PCP and 4‐Keto‐PCP may enhance their drug‐induced rewarding and reinforcing effects: Implications for abuse. (1st November 2020) - Ortiz, Darlene Mae; Custodio, Raly James Perez; Abiero, Arvie; Botanas, Chrislean Jun; Sayson, Leandro Val; Kim, Mikyung; Lee, Hyun Jun; Kim, Hee Jin; Jeong, Youngdo; Yoon, Sulmin; Lee, Yong Sup; Cheong, Jae Hoon
Abstract: Novel psychoactive substances remain the popular recreational drugs of use over the years. They continue to bypass government restrictions due to their synthesis and modifications. Recent additions to the lists are the 4‐F‐PCP and 4‐Keto‐PCP, analogs of the drug phencyclidine (PCP) known to induce adverse effects and abuse potential. However, studies on the abuse potential of 4‐F‐PCP and 4‐Keto‐PCP remain scarce. The rewarding and reinforcing effects of the drugs were assessed using conditioned place preference (CPP), self‐administration, and locomotor sensitization tests. Dopamine (DA) receptor antagonists (SCH23390 and haloperidol) were administered during CPP to evaluate the involvement of the mesolimbic dopaminergic system. DA‐related protein expression in the nucleus accumbens (NAcc) and ventral tegmental area (VTA) was measured. Additionally, phosphorylated cyclic‐adenosine monophosphate‐activated protein (AMP) response element‐binding (p‐CREB) protein, deltaFosB (∆FosB), and brain‐derived neurotrophic factor (BDNF) protein levels in the NAcc were measured to assess the addiction neural plasticity effect of the drugs. Both 4‐F‐PCP and 4‐Keto‐PCP‐induced CPP and self‐administration; however, only 4‐F‐PCP elicited locomotor sensitization. Treatment with DA receptor antagonists (SH23390 and haloperidol) inhibited the 4‐F‐ and 4‐Keto‐induced CPP. Both substances altered the levels of DA receptor D1 (DRD1), thyroxine hydroxylase (TH), DA receptor D2 (DRD2), p‐CREB, ∆FosB, and BDNF. The results suggest that 4‐F‐PCP and 4‐Keto‐PCP may induce abuse potential in rodents via alterations in dopaminergic system accompanied by addiction neural plasticity. Abstract : Pre‐treatment with SCH23390 (DRD1 antagonist) and haloperidol (DRD2 antagonist) showed that 4‐F‐PCP and 4‐Keto‐PCP may alter the dopaminergic system as seen in drugs with abused potential properties.